2001
DOI: 10.1053/euhj.2001.2691
|View full text |Cite
|
Sign up to set email alerts
|

New electrocardiographic leads and the procainamide test for the detection of the Brugada sign in sudden unexplained death syndrome survivors and their relatives

Abstract: Our data suggest that the new higher intercostal space lead ECG, with or without the procainamide test is helpful in detecting the Brugada sign in sudden unexplained death syndrome survivors and their relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(60 citation statements)
references
References 21 publications
6
53
0
1
Order By: Relevance
“…In addition to spontaneous ST-segment elevation and a history of syncope, the change in the ST-segment in the right precordial leads from a nondiagnostic to typical coved-type pattern after a sodium-channel blockade has been reported to be helpful for diagnosing and risk stratification for Brugada syndrome in survivors of cardiac arrests and their relatives. [18][19][20] However, more recently it has been shown that the drug provocation test may be negative in up to 80% of asymptomatic patients with normal resting ECG 20 and the response to sodium-channel blockade would not be specific for the Brugada syndrome but could be positive in other conditions such as cardiomyopathy and myocarditis. 5 In the present study, even with this limitation, the drug provocation tests in patients Nos.…”
Section: Circulation Journal Vol70 June 2006mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to spontaneous ST-segment elevation and a history of syncope, the change in the ST-segment in the right precordial leads from a nondiagnostic to typical coved-type pattern after a sodium-channel blockade has been reported to be helpful for diagnosing and risk stratification for Brugada syndrome in survivors of cardiac arrests and their relatives. [18][19][20] However, more recently it has been shown that the drug provocation test may be negative in up to 80% of asymptomatic patients with normal resting ECG 20 and the response to sodium-channel blockade would not be specific for the Brugada syndrome but could be positive in other conditions such as cardiomyopathy and myocarditis. 5 In the present study, even with this limitation, the drug provocation tests in patients Nos.…”
Section: Circulation Journal Vol70 June 2006mentioning
confidence: 99%
“…Second, a genetic analysis was not available. However, sodium-channel mutations have been identified in only a small portion of patients 18 and these mutations per se may not exclude an underlying organic heart disease. 5,23 …”
Section: Study Limitationsmentioning
confidence: 99%
“…A spontaneous coved-type ST elevation, inducible VF, and the loss-of-function SCN5A mutation are all consistent with the diagnosis of Brugada syndrome in this case that could potentially give rise to lethal arrhythmias. It was reported that some patients with Brugada syndrome, like the present case, exhibit only a coved-type ST elevationwhen the ECG is recorded from a higher intercostal space in the presence or absence of Na channel blockers 10,11 . Therefore, the proband suffered from two apparently distinct conditions: NMS and Brugada syndrome.…”
Section: Discussionmentioning
confidence: 50%
“…However, it has been reported that the ECG recorded at higher intercostal space is more sensitive and useful for diagnosis of Brugada syndrome than that recorded at the standard position. [14][15][16][17][18][19] In the present study, to avoid the risk of drug-induced ventricular tachyarrhythmias on drug testing, we analyzed baseline ECG parameters recorded at the standard position and the third intercostal space in individuals with SB-ECG, and evaluated predictors of PR on drug provocation testing. …”
mentioning
confidence: 99%